2022
DOI: 10.1038/s41467-022-29674-x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous variability in gamma dynamics described by a damped harmonic oscillator driven by noise

Abstract: Circuits of excitatory and inhibitory neurons generate gamma-rhythmic activity (30–80 Hz). Gamma-cycles show spontaneous variability in amplitude and duration. To investigate the mechanisms underlying this variability, we recorded local-field-potentials (LFPs) and spikes from awake macaque V1. We developed a noise-robust method to detect gamma-cycle amplitudes and durations, which showed a weak but positive correlation. This correlation, and the joint amplitude-duration distribution, is well reproduced by a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 69 publications
3
40
0
Order By: Relevance
“…Oscillations are ubiquitous in the emergent macroscopic activity of the brain, yet only those in the damped regime predominated among the optimal equations for the local dynamics. This result agrees with empirical results as well as with the dynamical repertoire of multiple models of large-scale brain activity, which feature transitions towards stable spirals through different bifurcations 22,38-40 . Finally, in the case of oscillatory dynamics (stable limit cycle), the presence of anharmonicities influenced the goodness of fit metrics, with departures from sinusoidal waveforms benefiting the reproduction of empirical FCD.…”
Section: Discussionsupporting
confidence: 89%
“…Oscillations are ubiquitous in the emergent macroscopic activity of the brain, yet only those in the damped regime predominated among the optimal equations for the local dynamics. This result agrees with empirical results as well as with the dynamical repertoire of multiple models of large-scale brain activity, which feature transitions towards stable spirals through different bifurcations 22,38-40 . Finally, in the case of oscillatory dynamics (stable limit cycle), the presence of anharmonicities influenced the goodness of fit metrics, with departures from sinusoidal waveforms benefiting the reproduction of empirical FCD.…”
Section: Discussionsupporting
confidence: 89%
“…firing variability) during states of strong gamma (Vinck and Bosman, 2016). The stochastic nature of the oscillations in this regime, as observed by Burns et al (2011); Spyropoulos et al (2022a), is critical because too strong synchronization is detrimental for coding (Chalk et al, 2016). Following the empirical observations of Uran et al (2022), we hypothesize that when inputs into the network become higher dimensional, the reconstruction error increases and the optimum shifts leftwards.…”
Section: Box 4: Measures Of Inter-areal Interactionsmentioning
confidence: 87%
“…We found that while visual stimulation reduces the frequency peak of alpha power (Figure 3D), high arousal states show consistently higher alpha peaks than low arousal states. Previous studies focused on gamma oscillations have found that this peak variability might reflect rapid cyclic changes in synaptic excitation (and a proportional inhibitory counterbalance) within a cortical microcircuit (Atallah and Scanziani 2009; Spyropoulos et al 2022). Our results show that this variability can also affect low frequency oscillatory components of the LFP.…”
Section: Discussionmentioning
confidence: 99%